Phase II, multicenter, randomized trial of CPX‐351 (cytarabine:daunorubicin) liposome injection versus intensive salvage therapy in adults with first relapse AML. Issue 2 (15th September 2014) - Cortes, Jorge E.; Goldberg, Stuart L.; Feldman, Eric J.; Rizzeri, David A.; Hogge, Donna E.; Larson, Melissa; Pigneux, Arnaud; Recher, Christian; Schiller, Gary; Warzocha, Krzysztof; Kantarjian, Hagop; Louie, Arthur C.; et al.
Abstract : BACKGROUND: CPX‐351 is a liposome‐encapsulated fixed‐molar‐ratio formulation of cytarabine and daunorubicin that exploits molar ratio–dependent drug‐drug synergy to enhance antileukemic efficacy. METHODS: This phase II study randomized 125 patients 2:1 to CPX‐351 or investigators' choice of first salvage chemotherapy. Patients with acute myeloid leukemia (AML) in first relapse after initial Complete Remission (CR) lasting ≥1 month were stratified per the European Prognostic Index (EPI) into favorable, intermediate, and poor‐risk groups based on duration of first CR, cytogenetics, age, and transplant history. Control salvage treatment was usually based on cytarabine and anthracycline, often with 1 or more additional agents. Survival at 1 year was the primary efficacy end point. RESULTS: Patient characteristics were well balanced between the 2 study arms. Improvements in efficacy outcomes were observed following CPX‐351, but did not meet prospectively defined statistical criteria for 1‐year survival improvement in the overall population. Subset analyses of the EPI‐defined poor‐risk strata demonstrated higher response rates (39.3% vs 27.6%) and improvements in event‐free survival (HR, 0.63; P  = .08) and overall survival (HR, 0.55; P  = .02). Also, 60‐day mortality was lower in the CPX‐351 study arm for poor‐risk patients (16.1% vs 24.1%). CONCLUSIONS: Taken together, the data suggest possible improved outcomes in CPX‐351‐treated first relapse AML patients with EPI‐defined poor‐risk disease. Cancer 2015;121:234–42 . © 2014 American Cancer Society . Abstract : CPX‐351, a liposome‐encapsulated fixed‐molar‐ratio formulation of cytarabine and daunorubicin, exploits molar ratio–dependent drug‐drug synergy to enhance antileukemic efficacy. A randomized phase II study comparing CPX‐351 with investigators' choice of first salvage therapy in first‐relapse patients demonstrated improved response, event‐free survival, and overall survival (HR, 0.55; P  = .02) in the poor‐risk strata.